Winter cover crop suppression methods influence on sunflower growth and rhizosphere communities - Morales, Marianela Estefanía; Allegrini, Marco; Basualdo, Jessica; Iocoli, Gastón Alejandro; Villamil, María Bonita; Zabaloy, María Celina (Frontiers in Microbiology, 2024)
Sunflower (Helianthus annuus L.), a vital crop for global vegetable oil production, encounters sustainability challenges in its cultivation. This study assesses the effects of incorporating a winter cover crop (CC), Avena sativa (L.), on the subsequent growth of sunflower crops and the vitality of their rhizosphere microbial communities over a two-year period. It examines the impact of two methods for suppressing winter CC-chemical suppression using glyphosate and mechanical suppression via rolling-both with and without the addition of phosphorus (P) starter fertilizer. These approaches are evaluated in comparison to the regional best management practices for sunflower cultivation, which involve a preparatory chemical fallow period and the subsequent application of starter P fertilizer. The methodology utilized Illumina sequencing for the analysis of rhizosphere bacterial 16S rRNA genes and fungal internal transcribed spacer (ITS) amplicons.Findings indicate a significant improvement (9-37%) in sunflower growth parameters (plant height, stem diameter, head diameter, and head dry weight) when cultivated after glyphosate-suppressed winter CC compared to the chemical fallows. Conversely, rolling of winter CC generally negatively affected sunflower growth. Rhizosphere bacterial communities following chemical suppression of winter CC showed greater Pielou's evenness, indicating a uniform distribution of species. In general, this treatment had more detrimental effects on beneficial sunflower rhizosphere bacteria such as Hymenobacter and Pseudarthrobacter than rolling of the winter CC, suggesting that the overall effect on sunflower growth may be mitigated by the redundancy within the bacterial community. As for fungal diversity, measured by the Chao1 index, it increased in sunflowers planted after winter CC and receiving P fertilization, underscoring nutrient management's role in microbial community structure. Significant positive correlations between fungal diversity and sunflower growth parameters at the reproductive stage were observed (r = 0.41-0.72; p < 0.05), highlighting the role of fungal communities in plant fitness.The study underscores the positive effects of winter CC inclusion and management for enhancing sunflower cultivation while promoting beneficial microbes in the crop's rhizosphere. We advocate for strategic winter CC species selection, optimization of mechanical suppression techniques, and tailored phosphorus fertilization of sunflower to foster sustainable agriculture.